Carbon nanotubes embedded in a polyimide foil for proton acceleration with a sub-ns laser. (5th July 2021) - Mangione, A.; Picciotto, A.; Margarone, D.; Malinowska, A.; Szydlowsky, A.; Velyhan, A.; Krasa, J.; Tomarchio, E.; Ganci, F.
Abstract: A series of thin films made of aligned carbon nanotubes (CNTs) embedded in a polyimide substrate was designed, fabricated and used for the first time to accelerate protons and C ions by interaction with a sub-nanosecond, high power laser beam (600 J energy and 300 ps pulse width) with peak intensity of about 3 × 10 16 W/cm 2 on target. Each target was 5 µm thick, and the composite material contained CNTs aligned in different directions in the substrate. The results obtained from the analysis of a Thomson Parabola spectrometer, and of the spots imprinted by ions on a series of PM355 nuclear track detectors, indicate high energies (up to 3 MeV for protons and 9 MeV for C ions) and a marked influence of the CNTs' orientation on the produced proton beam current. An increase of the proton fluxes, more than two orders of magnitude, was recorded with the targets containing CNTs aligned parallel to the target normal, in comparison to the other targets. The presented experimental results demonstrate that the laser-driven proton beam flux can be increased using ad hoc designed targets (with embedded and aligned nanotubes) and sub-nanosecond laser pulses with moderate intensities and poor temporal contrast, thus in an acceleration regime very far from those typically investigated experimentally using relativistic intensities (>5 × 10 18 W/cm 2 ) and short laser pulses (10 fs to 10 ps).